PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION KARYAWAN PADA KRISNA OLEH-OLEH KHAS BALI III - Bramantara, Gusti Ngurah Berlin; Kartika Dewi, Anak Agung Sagung (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the effect of job satisfaction and organizational commitment on employee turnover intention in Krisna Oleh-Oleh Khas Bali III. This study used a quantitative research by using surveys and questionnaires to 75 employees Krisna Oleh-Oleh Khas Bali III. This study receipts data analysis techniques of multiple linear regression. Obtained findings that simultaneous variables job satisfaction and organizational commitment affect turnover intention of employees in Krisna Oleh-Oleh Khas Bali III. Other results found that partially can be seen that the variable job satisfaction and organizational commitment and a significant negative effect on employee turnover intention Krisna Oleh-Oleh Khas Bali III. Finally, organizational commitment variable is a variable that has a dominant influence on employee turnover intention in Krisna Oleh-Oleh Khas Bali III.
Keywords: Kepuasan Kerja; Komitmen Organisasi; Turnover Intention